Hubungan antara Pemberitaan Pembatasan 17 Lagu Barat oleh KPID Jawa Barat terhadap Minat Pendengar Lagu Barat di Radio - Nadya Savira Chaerani; Dedeh Fardiah (Jurnal Riset Jurnalistik dan Media Digital, 2021)
Abstract. In February 2019 KPID West Java issued a circular containing restrictions on the hours of broadcast of some English-language songs that were vulgar in content, both in the form of songs or video clips. There are 17 English songs contained in circular attachments issued by KPID West of Java. Dozens of songs can only be aired starting at 22:00 WIB until 03.00 WIB. The broadcast limitation starts from public complaints and KPID supervision of the broadcast content. A number of online media rollicking to preach this event, one of which is online media Detik.com which is a news site that is widely accessed by various groups. This study uses a quantitative method with a correlational approach that aims to find out the relationship of truth, relevance, balance and neutrality between the coverage of 17 western songs by KPID West of Java towards the interests of listeners of western songs on Radio as aspects of cognitive, evaluative and the interests of listeners of western songs on the radio The students of Faculty of Communication Sciences Unisba as the dependent variable, this study uses the objectivity theory of Westerstahl. From this study using the stratified random sampling technique, it was concluded that there was a significant and very strong relationship between Factuality, Impartiality and Western Song Listeners' Interests on Radio at the Faculty of Communication Sciences Unisba. Abstrak. Pada bulan Februari 2019 KPID Jawa Barat mengeluarkan surat edaran yang berisi tentang pembatasan jam penyiaran beberapa lagu berbahasa Inggris yang berkonten vulgar, baik dalam bentuk lagu atau pun video klip. Terdapat 17 lagu berbahasa Inggris yang terdapat dalam lampiran surat edaran yang dikeluarkan KPID Jawa Barat. Belasan lagu itu hanya boleh tayang mulai pukul 22.00 WIB hingga 03.00 WIB. Pembatasan penyiaran berawal dari aduan masyarakat dan pengawasan KPID terhadap isi siaran. Sejumlah media online beramai-ramai memberitakan peristiwa ini salah satunya media online Detik.com yang merupakan situs berita yang banyak diakses oleh berbagai kalangan. Penelitian ini menggunakan metode kuantitatif dengan pendekatan korelasional yang bertujuan mengetahui adanya hubungan kebenaran, relevansi, keberimbangan dan netralitas antara pemberitaan pembatasan 17 lagu barat oleh KPID Jawa Barat terhadap minat pendengar lagu barat di Radio sebagai aspek dalam kognitif, evaluatif dengan minat pendengar lagu barat di radio pada Mahasiswa Fikom Unisba sebagai variabel terikat, penelitian ini menggunakan teori Objektivitas dari Westerstahl. Dari penelitian ini yang menggunakan teknik penarikan sampel stratified random sampling ini ditemukan kesimpulan, bahwa terdapat hubungan yang signifikan dan sangat kuat antara Faktualitas, Imparsialitas dengan Minat Pendengar Lagu Barat di Radio pada Mahasiswa Fikom Unisba.